The mapping of forms of spatial planning: An instrument-oriented tool for the international comparison of spatial planning activities - Salamin, Géza (European Spatial Research and Policy, 2023)
The paper makes a contribution to European comparative research on spatial planning by providing an instrument-oriented methodological framework for forms of planning. Based on the main efforts to date, the main challenges of comparative research on European planning systems are identified. The author’s comparative four-dimensional model and related visual tool can be used to bridge different national languages of planning and compare various spatial forms of planning. With the tool, the nature of planning regimes, specific plans, and other planning-related activities can be identified in accordance with the dimensions of Motivation, Geography, Scope, and Instruments, making them comparable.